Complications following comminuted femoral shaft fractures treated with interlocking nail with or without inter fragmentary screw fixation for butterfly fragment: case series - kaliamurthy, Muthukumar; Elumalai, Rajarajan; Subramaniyan, Vijay Krishnan Arcot (International Journal of Research in Orthopaedics, 2017)
Background: This case series is to highlight the complications following interfragmentary compression screw fixation for butterfly fragment while treating femoral shaft fractures with interlocking nail. Methods: Twelve cases have been included in this study conducted in institute of orthopaedics and traumatology, MMC & RGGGH, Chennai. All patients had shaft of femur fracture with butterfly fragment for which open reduction and interlocking nailing done. For 6 patients we applied interfragmentary screws for the butterfly fragment and in rest of the patients (6) patients we left the butterfly fragment in situ without disturbing the soft tissue attachment and bone grafting for the bone gap where ever necessary. We followed up the patient at 3 weeks, 6 weeks and 12 weeks, 6 months and 12 months. Results: All the six patients fixed with inter fragmentary screws had wound infection and went for infected nonunion for which appropriate management was done including revision nailing or LRS application. Union was achieved in 12 to 16 months after various surgical interventions. Remaining six patients in whom interfragmentary screws were not applied and primary bone grafting when and where necessary was done, showed radiological union by three months. Conclusions: Blood supply to large butterfly fragment is the main key for the healing process not the near normal anatomical reduction using interfragmentary screw for the butterfly fragment. Relative stability is enough for fracture union. In bone defects arising out of comminution primary bone grafting is essential for the bone healing.